Sugar-Sweetened Beverages and Depressive and Social Anxiety Symptoms Among Children and Adolescents Aged 7–17 Years, Stratified by Body Composition - Liu, Jieyu; Chen, Ting; Chen, Manman; Ma, Ying; Ma, Tao; Gao, Di; Li, Yanhui; Ma, Qi; Chen, Li; Wang, Xinxin; Zhang, Yi; Ma, Jun; et al. (Frontiers in Nutrition, 2022)
Background: Rare studies investigated associations between sugar-sweetened beverage (SSB) consumption with depressive and social anxiety symptoms among children and adolescents, particularly in different stratification of body composition, which was our purpose. Methods: A cross-sectional survey of children and adolescents aged 7-17 years was conducted in Beijing of China in 2020, with the average age of 12.07 (SD: 3.09) years old. Children’s Depression Inventory (CDI) questionnaires and social anxiety scale for children (SASC) were completed in the baseline questionnaires. SSB consumption and body composition were assessed using child-reported questionnaires and a GE Healthcare Lunar iDXA dual-energy X-ray bone densitometer. Multivariate logistic regression was used to assess the associations between SSB consumption with depressive and social anxiety symptoms. Confounders were evaluated by child-reported and parental questionnaires, including age, sex, parental educational attainment, maternal smoking status, single-child status, BMI, incomes, fruit consumption, physical activity, screen time and the frequency of fried food consumption. Stratified analyses were performed to explore whether the associations were influenced by body composition. Results: A total of 1311 children and adolescents including 658 boys and 653 girls were included in the final analysis. There were 13.96% and 29.75% of study population with depression and social anxiety symptoms, respectively. Overall, about 63.77% of the children and adolescents consumed SSB, and the average SSB intake was 0.35 servings per day. In the fully adjusted model, compared to participants who did not consume SSB each day, SSB consumption of ≥1 servings /day was positively associated with depressive symptoms (OR=2.28, 95%CI=1.30-4.01) and social anxiety (OR=1.10, 95%CI=0.69-1.77), though the latter did not reach statistical significance. When individuals had higher body fat or lower fat-free mass or muscle, the odds of depressive symptoms were more evident among children and adolescents who drank SSB for ≥1 servings /day (P <0.05). Conclusion: Higher consumption of SSB could be associated with increased odds of depressive symptoms in children and adolescents. The association remained robust especially in groups with higher body fat or lower fat-free or muscle.